Hubungan Pola Asuh, Sumber Informasi Dan Gizi Terhadap Tumbuh Kembang Pada Balita Usia 1-5 Tahun Di Desa Gintung Cilejet : The Relationship between Parenting, Information Sources, and Nutrition on Growth and Development in Toddlers Aged 1-5 Years in Gintung Village, Cilejet - Pauji, Reksa; Shinta Mona Lisca (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Children are an investment and hope for the future of the nation and the next generation to come. The growth and development of children is very important. The future of a nation depends on the success of the child in achieving optimal growth and development. Methods: This type of research is a quantitative study with a cross-sectional study design. This research was conducted in February 2021 the population is mothers who have toddlers aged 1-5 years who were taken door to door in the village of Gintung Cilejet with as many as 89 respondents with purposive sampling data collection technique. This study uses an instrument in the form of a questionnaire sheet. The analysis method used chi-square with SPSS 21. Results: The results of the analysis showed Parenting Patterns (P = 0,001); Information Sources (P = 0,001); and Nutritional (P = 0,001) that H0 was rejected because 3 independent variables had p-value < 0,005; which means that their relationship between parenting styles, information sources, and nutritional status for growth and development in toddlers aged 1-5 years in Gintung Cilejet Village, Parung Panjang District in 2021. Discussion: Suggestions for Gintung Cilejet Village are expected to be able to advocate and provide health promotion to mothers who have toddlers regarding the importance of knowing the development of toddlers so that it can help prevent deviations in toddler growth and development